Factors Predicting Sleep Quality Among Nursing Students - นันท์ชัย จิราภรณ์; ใคร้ศรี นริศรา; สมบูรณ์ ลาวัลย์; ทองสวัสดิ์ เทียมศร (Nursing Journal CMU, 2017)
Sleep quality of nursing students is an indicator of both physical and mental health affecting the quality of learning and graduation success. The purpose of this predictive correlational descriptive study was to determine predictive factors of sleep quality among nursing students such as age, college year, grade point average (GPA), sleep habits and stress. The participants were 217 nursing students of freshman, sophomore, junior, and senior classes of one nursing college from April to May 2017. Proportionate stratified random sampling was used. Data were collected using 1) the sleep habits questionnaire which showed the content validity index of 1, 2) the Suanprung Stress Test (Mahatnirunkul, Pumpaisarnchai & Tapunya, 1997), and 3) the Pittsburgh Sleep Quality Index (Jirapramukpitak & Tanchaiswad, 1997). The last three scales showed the reliability of Cronbach’s alpha efficiency of .70, .96 and .80, respectively. Data were analyzed using descriptive statistics, and enter logistic regression. Results of the study showed that More than half of the samples (66.36 %) had poor sleep quality. Age, college year, GPA, sleep habits, and stress were accounted for 27.5% in sleep quality (Nagelkerke R2 = .275). Sleep habits and stress significantly predicted sleep quality (OR = .23; 95% Cl = .09-.57, p<.01 and OR = 2.91; 95% Cl = 1.81-4.67, p<.01 respectively). The results of this study is useful for educational institution administrators and nursing instructors to promote students to have good sleep quality by means of providing activities to promote good sleep habits, using appropriate relaxing techniques starting in their freshman year as well as monitoring continuously until graduation.